Mutation of serine 1333 in the ATR HEAT repeats creates a hyperactive kinase. - Jessica W Luzwick; Edward A Nam; Runxiang Zhao; David Cortez (PLoS ONE, 2014)
Subcellular localization, protein interactions, and post-translational modifications regulate the DNA damage response kinases ATR, ATM, and DNA-PK. During an analysis of putative ATR phosphorylation sites, we found that a single mutation at S1333 creates a hyperactive kinase. In vitro and in cells, mutation of S1333 to alanine (S1333A-ATR) causes elevated levels of kinase activity with and without the addition of the protein activator TOPBP1. S1333 mutations to glycine, arginine, or lysine also create a hyperactive kinase, while mutation to aspartic acid decreases ATR activity. S1333A-ATR maintains the G2 checkpoint and promotes completion of DNA replication after transient exposure to replication stress but the less active kinase, S1333D-ATR, has modest defects in both of these functions. While we find no evidence that S1333 is phosphorylated in cultured cells, our data indicate that small changes in the HEAT repeats can have large effects on kinase activity. These mutants may serve as useful tools for future studies of the ATR pathway.